THE CONSTRUCTION OF MEANING IN THE TEXT “THERE’S NO PEACE IN BOARD OF PEACE. FREE PALESTINE” IN THE STAGE VISUALS OF FEAST’S CONCERT: A PRAGMASEMANTIC STUDY - Aisyah Sahla Saudah; Nafsiyah Puspa Pratiwi; Siti Humairoh; Tatu Siti Rohbiah (Asosiasi dosen IDEBAHASA KEPRI, 2026)
Language in visual media does not merely function as a decorative element, but also as a semiotic unit that actively constructs and conveys meaning. This study examines the construction of meaning in the text